PERBEDAAN PENGEMBANGAN KEGIATAN PROFESI KONSELOR: DITINJAU DARI â€œBELUM DAN SUDAHâ€ MEMPEROLEH SERTIFIKAT PENDIDIK - Lusiana, Anies; Poerwanti, Endang (Jurnal Kebijakan dan Pengembangan Pendidikan, 2016)
Abstract: The purpose of this study to describe and analyze the differences in professional development. The purpose of this study to describe and analyze the differences in professional development activities and the counselors that have not been certified in junior derby Pasuruan. This research used a descriptive research comparative quantitative approach. The population in this study is junior counselors of Pasuruan many as 35 people. Data collection techniques by distributing questionnaires to the respondents. Data analysis was performed using descriptive analysis and comparative analysis. The analysis showed that the pedagogical counselor who has been certified by 83% with a performance score of 15 and counselors are not certified as much as 67% with a performance score of 12 out of a maximum score is 18. The personal competence counselor has been certified as much as 85% with a score of 24 and performance counselors are not certified as much as 64% with a performance score of 18 out of a maximum score is 28. social competence counselor who has been certified as much as 86% with a performance score of 19 and counselors that have not been certified as much as 64% with a performance score of 14 out of a maximum score is 22. the professional competence of counselor who has been certified by 32% with a performance score of 23 and counselors are not certified as much as 15% with a performance score of 11 out of the maximum score is 72.Keywords: Counselor profession, Competence counselor, Educator certification Abstrak: Tujuan dari penelitian ini mendeskripsikan dan menganalisis perbedaan kegiatan pengembangan profesi konselor yang belum dan yang sudah sertifikasi di SMP sekota Pasuruan. Penelitian ini menggunakan jenis penelitian deskriptif komparatif pendekatan kuantitatif. Populasi dalam penelitian ini adalah konselor SMP SekotaPasuruan sebanyak 35 orang. Teknik pengumpulan data dengan cara membagikan angket kepada responden. Analisis data dilaksanakan menggunakan analisis deskriptif dan analisis komparatif. Hasil analisis menunjukkan menunjukkan bahwa kompetensi pedagogik Guru BK/Konselor yang sudah sertifikasi sebanyak 83% dengan skor capaian 15 dan Guru BK/Konselor yang belum sertifikasi sebanyak 67% dengan skor capaian 12 dari skor maksimal yaitu 18. Sedangkan kompetensi kepribadian Guru BK/Konselor yang sudah sertifikasi sebanyak 85% dengan skor capaian 24 dan Guru BK/Konselor yang belum sertifikasi sebanyak 64% dengan skor capaian 18 dari skor maksimal yaitu 28. Kompetensi sosial Guru BK/Konselor yang sudah sertifikasi sebanyak 86% dengan skor capaian 19 dan Guru BK/Konselor yang belum sertifikasi sebanyak 64% dengan skor capaian 14 dari skor maksimal yaitu 22. Sedangkan kompetensi professional Guru BK/Konselor yang sudah sertifikasi sebanyak 32% dengan skor capaian 23 dan Guru BK/Konselor yang belum sertifikasi sebanyak 15% dengan skor capaian 11 dari skor maksimal yaitu 72.Kata kunci: Profesi konselor, Kompetensi konselor, Sertifikasi pendidik